Phylogenetic Relationships Of The Sarawak Microhyla (Amphibia: Anura: Microhylidae) - Nooraina Atira, Alaudin (Universiti Malaysia Sarawak (UNIMAS), 2014)
Microhylidae was the one the families of anuran that can be found in Sarawak. The genus Microhyla (M. borneensis, M. berdmorei, M. malang, M. nepenthicola, M petrigena and M. perpava) were used in this study because of their poor understanding in the phylogenetic study. The samples were collected from four study areas which were Kubah National Park, Matang Wildlife Centre, Gunung Gading National Park and Gunung Santubong. The species and the outgroup species was collected using the forest transect and stream transects and the tissues were extracted for molecular study. The 16S ribosomal RNA gene was used to infer the phylogenetic relationships of the genus Microhyla through the Polymerase Chain Reaction (PCR). A total of 927 base pairs of 16S rRNA from 11 samples were analysed using Molecular Evolutionary Genetic Analysis 5.0 (MEGA 5.0). Then, the phylogenetic trees were constructed using Maximum Parsimony (MP), Neighbour Joining (NJ) and Maximum- Likehood (ML) and the genetic distances was calculated by using Kimura 2- parameter. All trees produced similar tree phylogram showed that the genus was monophyletic to the outgroup. It also proven that the 16S rRNA gene was useful as genetic marker for the phylogenetic study within then genus level.